Sources of Psychological Stress in the National Teams Players in the Sultanate of Oman - Almur M. Al-Hashmi (Sultan Qaboos University, 2016)
This study aimed to investigate the sources and levels of stress among the players of national teams in the Sultanate of Oman. It was of interest to identify the differences in the sources of stress among player in light of some variables: qualifications, game, age, marital status and monthly income. The researcher developed a questionnaire consisting of 62 items. The study was developed after verifying the sincerity and persistence of a sample of 111 players from the national team players. The results indicated that players experienced 22 out of 62 acute pressures. The results also showed that the order of the fields of psychological pressures for national team players is as follows: psychological stress associated with the media and the public, psychological stress associated with the technical and administrative system, psychological stress associated with the duties of training, psychological stress associated with a player's lifestyle, and psychological stress associated with competition.